Effect of milling time on the properties of Pb(Mg1/3Nb2/3)O3 ceramics using the starting precursors PbO and MgNb2O6 - Chaipanich A. (2014)
Lead magnesium niobate, Pb(Mg1/3Nb2/3)O3 (PMN) ceramics were prepared from the columbite method using calcined powders of various milling time (24-96 h). The effects on the grain size and dielectric properties of the ceramics were investigated. The results show that dielectric properties of ceramics are strongly influenced by the milling time of the starting precursors. Higher percentage of perovskite phase was found in the ceramics that was milled longer and thus the dielectric constant was found to increase when compared to the conventional 24 h milled results. Moreover, milling time also affected the particle size of the starting precursors and that of PMN powders. Therefore, milling time did not only affect the particle size of PMN powders but also the resultant grain size and the formation of perovskite phase, consequently affecting the dielectric constant of the ceramics. © 2006 Elsevier B.V. All rights reserved.